2009
DOI: 10.4049/jimmunol.0803765
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1 Suppresses Collagen-Induced Arthritis by Indirectly Providing a Negative Signal in CD8+ T Cells

Abstract: Distinct Notch ligands possess a characteristic ability in terms of functional T cell differentiation. However, the precise role or the therapeutic potential of each Notch ligand in autoimmune diseases is largely unknown. In this study, we examined whether Jagged1 modulates a collagen-induced rheumatoid arthritis (CIA) model by altering T cell responses. The injection of a soluble Jagged1-encoding plasmid, sJag1-P, before or even after initial type II collagen (CII) immunization suppressed the disease severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…DLL1 and 4 induced development of Th1 cells and effector memory CD8 + T-cells (15,2529), whereas Jagged1 and 2 skewed T-cells into Th2, Treg, and anergic CD8 + T-populations (16,3033). In agreement with the proposed immune inhibitory role of Jagged, we found that anti-Jagged overcame tumor-T-cell suppression through the induction of potentially immunogenic MDSC-LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DLL1 and 4 induced development of Th1 cells and effector memory CD8 + T-cells (15,2529), whereas Jagged1 and 2 skewed T-cells into Th2, Treg, and anergic CD8 + T-populations (16,3033). In agreement with the proposed immune inhibitory role of Jagged, we found that anti-Jagged overcame tumor-T-cell suppression through the induction of potentially immunogenic MDSC-LC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NICD triggers a number of non-canonical responses (11,12). Binding of the Notch receptors on CD8 + T-cells to DLL ligands on antigen-presenting cells induces anti-tumor cytotoxic responses (1315), whereas binding of Notch to Jagged members resulted in suppressive signals (16). The mechanism for this opposite effect remains unclear with possible explanations, including different kinetics of Notch activation or selectivity of DLL and Jagged ligands for Notch receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of Notch signalling by a γ-secretase inhibitor suppressed the progression of experimental autoimmune encephalomyelitis (EAE) 15. In contrast, overexpression of Jagged-1 suppressed CIA, and the blockade of Jagged-1 by an anti-Jagged-1 monoclonal antibody exacerbated CIA 11. Another report demonstrated that the administration of anti-Jagged-1 mAb exacerbated the clinical features of EAE, whereas DLL-1 mAb reduced disease severity 42.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and activation of Notch occur in osteoarthritis cartilage and RA synoviocytes 7–10. Notch signalling is involved in the TNFα-induced proliferation of RA synoviocytes,10 and Jagged-1 can modulate collagen-induced arthritis (CIA) progression by affecting CD8 + T cell responses 11. T helper (Th) cells from RA patients exhibit an altered expression profile of Notch receptors and enhanced activation of Notch signalling 12.…”
Section: Introductionmentioning
confidence: 99%
“…42 43 Jagged-1 modulates CIA by regulating T cell responses. 44 Notch-1 can mediate TNFα-induced synoviocyte proliferation, 42 45 and Notch-3 and DLL-1 mediate collagen-specific T-cell activation and altered T helper cells responses. 46 However, the mechanisms by which Notch signalling regulates angiogenesis in the inflamed joint remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%